Meta Analisis : Pengaruh Ukuran Perusahaan, Kepemilikan Institusional, Leverage, Terhadap Earnings Management - Khomara, Rania; Wuga, Silviana; Handayani, Maria Vania; Meiden, Carmel (Universitas Malahayati, 2023)
This study aims to integrate the effect of firm size, leverage, and institutional ownership on earnings management. Supervision of agents is carried out through a governance mechanism so that the actions of agents are in line with the principal's objectives. The research method used is a meta-analysis study. Earnings management journal articles publications are searched using the PoP application with a period limit of 2017-2022. A total of 30 samples of articles used purposive sampling method with a total of 200 data samples for 5 years. The results of the integration obtained in this study are firm size, institutional ownership, and leverage have a positive effect on the practice of Earnings Management